Design and development of a table top indoor herb or vegetable planter box - Rosete, Wilson Jerome Mendoza (2019)
Urban agricultural practices are constantly studied and explored to find new and innovative ways to improve efficiency, increase yield and raise the quality of food produced as an alternative to traditional farming methods. Growing food such as vegetables and herbs indoors can be a challenge especially with the absence of natural elements essential for plant growth. Hence the aim of this project is to construct a table top planter box that can cater for the successful growth of vegetables and herbs indoors while providing them with a suitable environment and the conditions they would require to grow. Topics on common adopted agricultural methods such as Geoponics, Hydroponics and Aeroponics, as well as existing systems available in the industry will be covered in this project. Lastly, this project will discuss in detail, design factors and considerations, steps taken for the production of the prototype, challenges and limitations faced and last but not least, future developments and improvements.